PENGEMBANGAN MATERI AJAR TEKS BERITA BERBANTUAN APLIKASI KVISOFT FLIPBOOK MAKER PADA SISWA KELAS VII SMP - Lestari Harefa, Dyana; Hutagalung, Trisnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to develop news text teaching materials, describe the product form, and test the feasibility level of the teaching materials with the help of the Kvisoft Flipbook Maker application for seventh grade junior high school students. The research method used is Research and Development (R&D) by adapting the Borg and Gall model which is simplified into five main stages, namely: 1) potential and problems, 2) data collection, 3) product design, 4) design validation, and 5) product design revision. This research was conducted at SMP Negeri 8 Percut Sei Tuan in the even semester of the 2025/2026 academic year involving 30 seventh grade students as research subjects. The results of the study show that the resulting product is an interactive digital book that integrates text and animation aspects, and is equipped with supporting colors and decorations to attract students' interest and curiosity, thereby increasing their learning motivation. Based on the final assessment, this product obtained a material feasibility score of 90% (Very Feasible) and a media feasibility score of 94.5% (Very Feasible). Thus, it can be concluded that the news text teaching material based on the Kvisoft Flipbook Maker application is very suitable for use as a supporting medium for digital learning at the secondary school level.